The Effect of Orally Administered Ranitidine and Once‐Daily or Twice‐Daily Orally Administered Omeprazole on Intragastric pH in Cats. (13th May 2015) - Šutalo, S.; Ruetten, M.; Hartnack, S.; Reusch, C.E.; Kook, P. H.
<x xml:space="preserve">Abstract</x> Background Gastric acid suppressants frequently are used in cats with acid‐related gastric disorders. However, it is not known if these drugs effectively increase intragastric pH in cats. Objectives To examine the effects of PO administered ranitidine and omeprazole on intragastric pH in cats and to compare the efficacy of once‐daily versus twice‐daily dosage regimens for omeprazole. Animals Eight domestic shorthair cats. Methods Using a randomized 4‐way cross‐over design, cats were given enteric‐coated omeprazole granules (1.1–1.3 mg/kg q24h and q12h), ranitidine (1.5–2.3 mg/kg q12h), and placebo. Intragastric pH was monitored continuously for 96 hours using the Bravo™ system, starting on day 4 of treatment, followed by a median washout period of 12 days. Mean percentage of time pH was ≥3 and ≥4 was compared among groups using repeated measures ANOVA. Results Mean ± SD percentage of time intragastric pH was ≥3 and ≥4 was 67.0 ± 24.0% and 54.6 ± 26.4% for twice‐daily omeprazole, 24.4 ± 22.8% and 16.8 ± 19.3% for once‐daily omeprazole, 16.5 ± 9.0% and 9.6 ± 5.9% for ranitidine, and 9.4 ± 8.0% and 7.0 ± 6.6% for placebo administration. Twice‐daily omeprazole treatment significantly increased intragastric pH, whereas pH after once‐daily omeprazole and ranitidine treatments did not differ from that of placebo‐treated cats. Conclusion and Clinical Importance Only twice‐daily PO administered omeprazole significantly suppressed gastric acidity in healthy cats, whereas once‐daily omeprazole and standard dosages of ranitidine were not effective acid suppressants in cats.